Peran Pemerintah Daerah Kota Bogor Dalam Pelaksanaan Urusan Pemerintahan di Bidang Lalu Lintas dan Transportasi: The Role Of The Bogor City Regional Government In Implementing Government Affairs In The Field Of Traffic And Transportation - Sacharissa Kaulika; Ninuk Wijiningsih (Faculty of Law, Universitas Trisakti, 2024)
Based on Bogor City Regional Regulation Number 8 of 2023 and Bogor City Regional Regulation Number 10 of 2019, the Regional Government of Bogor City has the authority to regulate transportation and traffic in the City of Bogor. The problem of this research is whether the efforts made by the Bogor City Regional Government in the field of transportation are in accordance with Bogor City Regional Regulation Number 8 of 2023? and what are the obstacles for the Bogor City Government in enforcing regulations in the transportation sector and the solutions. This research is a type of normative legal research, deductive in nature, using secondary data as the main data, analyzed qualitatively, and drawing conclusions deductively. The conclusion of this research is Regional Government of the City of Bogor controlling and regulating transportation and traffic in the City of Bogor, in this case has tried to control and regulate transportation, but there are still obstacles and it has not been maximized, which causes the traffic transportation regulations in the area to be imperfect. The city of Bogor and limited infrastructure exacerbate transportation problems in this city. The Government needs to take strategic steps to increase public awareness through traffic safety.